The advisers scientists in the policy process - Smith, Bruce L. R. 1936- (Brookings Inst., 1992)
America's governing system is unique in the extent to which scientists and other outside experts participate in the policy process. No other nation uses these experts so extensively, not merely for advice on the allocation of resources to science but also in broad policy issues. This wide-ranging study traces the rise of scientists in the policy process and shows how outside experts interrelate with politicians and administrators to produce a unique and dynamic policy process. It also shows how the very openness of American government creates the potential for unusual conflicts of interest. Bruce Smith focuses on the experience of agency and presidential-level advisory systems over the past several decades. He chronicles the special complexities and challenges resulting from the Federal Advisory Committee Act--the "open meeting" law--to provide a better understanding of the role of advisory committees and offers valuable lessons to guide their future use